2021
DOI: 10.1016/j.midw.2021.103069
|View full text |Cite
|
Sign up to set email alerts
|

“Anxious and traumatised”: Users’ experiences of maternity care in the UK during the COVID-19 pandemic

Abstract: Objective The COVID-19 pandemic saw universal, radical, and ultra-rapid changes to UK National Health Services (NHS) maternity care. At the onset of the pandemic, NHS maternity services were stripped of many of the features which support woman and family centred care. In anticipation of unknown numbers of pregnant women and maternity staff potentially sick with COVID-19, services were pared back to the minimum level considered to be required to keep women and their babies safe. The aim of this sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 7 publications
(7 reference statements)
6
79
0
1
Order By: Relevance
“…Women reported feeling like a bother when they asked for help and felt that the postnatal wards were critically understaffed. Similar findings are presented in a recent study from UK, were women reported feeling isolated and sad in the postnatal period and frustrated and upset by a lack of staff to help them care for the new baby ( Sanders & Blaylock, 2021 ). Our findings indicate that individual breastfeeding support was one of the aspects of early postnatal care that suffered the most.…”
Section: Discussionsupporting
confidence: 86%
“…Women reported feeling like a bother when they asked for help and felt that the postnatal wards were critically understaffed. Similar findings are presented in a recent study from UK, were women reported feeling isolated and sad in the postnatal period and frustrated and upset by a lack of staff to help them care for the new baby ( Sanders & Blaylock, 2021 ). Our findings indicate that individual breastfeeding support was one of the aspects of early postnatal care that suffered the most.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the emerging evidence that many women have greatly appreciated having fewer visitors in hospital, not all studies into this topic have demonstrated positive results. Recent data from a United Kingdom- based study found that the majority of birthing women surveyed were displeased with COVID-19- related hospital visitor restrictions, with 72% stating that the restrictions had led to increased feelings of loneliness ( Sanders & Blaylock, 2021 ). However, women in this context reported that one of the key elements which caused them to feel negatively about the restrictions was that they had less interaction with the midwives during their hospital stay ( Sanders & Blaylock, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence supporting the emotional, psychological and physical trauma inflicted on women who experienced visitor restrictions while receiving maternity care after 11 March 2020 during the COVID-19 pandemic. 1 The study employed the quantitative and qualitative format to demonstrate the number of women who experienced this trauma from the implementation of visitor's restrictions in the UK maternity ward. 1…”
Section: Contextmentioning
confidence: 99%
“…The women reported an escalation of anxiety and sadness particularly in the postpartum period. 1 For some, this emotional state had an impact on their recovery, while others reported a negative impact on their ability to care for their newborns. 1 As this pandemic is approaching to an end, we are left to live in a new normal.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation